Patient empowerment interacts with health literacy to associate with subsequent self-management behaviors in patients with type 2 diabetes: A prospective study in Taiwan. Issue 10 (October 2016) - Wang, Ruey-Hsia; Hsu, Hui-Chun; Lee, Yau-Jiunn; Shin, Shyi-Jang; Lin, Kun-Der; An, Ling-Wang
Highlights: Empowerment interacts with health literacy to influence self-management behaviors of patients. Empowerment may improve self-management behaviors in patients with high health literacy. Empowerment may be useless on self-management behaviors in patients with low health literacy. Abstract: Objective: To examine association of interactions between patient empowerment (PE) and health literacy with 1-year-later self-management behaviors in patients with type 2 diabetes (T2DM). Methods: A prospective design was employed in this study. Overall, 395 patients with T2DM completed self-reported questionnaires at baseline and 1 year later. A hierarchical multiple regression was used to identify the association of interactions between PE and health literacy at baseline with the 1-year-later self-management behaviors. Results: Interactions between PE and communicative and critical health literacy (CCHL) at baseline significantly associated with the 1-year-later global self-management behaviors in patients with T2DM. Among the participants who exhibited high PE at baseline, the scores of 1-year-later global self-management behaviors of the participants with a high CCHL at baseline were significantly higher than those with a low CCHL at baseline. Nevertheless, among the participants who exhibited low PE at baseline, no significant differences were identified in the 1-year-later global self-management behaviors between the participants with high vs. low CCHL at baseline. Conclusions: PE may improve self-management behaviors in patients with high CCHL, but may prove useless in patients with low CCHL. Practice implications: Healthcare providers should ensure that patients with T2DM have adequate CCHL prior to empowering them.